Analisis Kualitas Butir Soal Asesmen Sumatif Matematika Pilihan Ganda Semester Genap Kelas VIII MTs Baitul Ma’mur Tahun Ajaran 2023/2024: Analysis of the Quality of Multiple-Choice Mathematics Summative Assessment Items for the Even Semester of Grade VIII at MTs Baitul Ma'mur in the 2023/2024 Academic Year - Abdullah, Ikhsan; Listyotami, Mega Kusuma; Ferita, Rolina Amriyanti; Lisa, Lisa; Maulida, Dina; Yanti, Williza; Hidayat, Farid (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The goal of this study was to evaluate the quality of multiple-choice summative assessment questions in mathematics at MTs Baitul Ma'mur, even semester, grade VIII, academic year 2023/2024, using a validity test, difficulty level test, reliability test, distractor test, and discriminating power test. This study strategy employs a quantitative approach in the form of a descriptive analysis of 20 pupils. Data are supplied as question sheets, answer sheets, and answer keys. The data were analyzed using percentage description approaches obtained from Excel data processing. According to the findings of this study, the validity test contained three questions with low validity and eight questions with very poor validity. However, the results of the reliability test on the question showed a high level of consistency, and the difficulty level of the test on the question was moderate, indicating that the level of difficulty was in the good range. Furthermore, the findings of the discriminating power test on the question were incorporated into the good and useful category. Furthermore, the results of the distraction effectiveness test on the question were factored into the functional criteria. So, the multiple-choice summative assessment questions for mathematics topics at MTs Baitul Ma'mur, even semester, grade VIII, 2023/2024 academic year are deemed satisfactory, although the validity portion might be enhanced.